Use Cramer's Rule to solve the following system of equations. Write each answer in simplest form. \[ \begin{array}{r}-4 x+9 y-z=-8 \\ 2 x-3 y-6 z=4 \\ 3 x-5 y-9 z=6\end{array} \] Write the four relevant determinants in any order:
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To use Cramer's Rule, we need to calculate the determinants of the coefficient matrix and the matrices formed by replacing each column with the constants from the right-hand side of the equations. The coefficient matrix \( A \) is: \[ A = \begin{bmatrix} -4 & 9 & -1 \\ 2 & -3 & -6 \\ 3 & -5 & -9 \end{bmatrix} \] ### 1. Calculate the determinant of \( A \) (denoted as \( D \)): \[ D = \begin{vmatrix} -4 & 9 & -1 \\ 2 & -3 & -6 \\ 3 & -5 & -9 \end{vmatrix} = -4 \begin{vmatrix} -3 & -6 \\ -5 & -9 \end{vmatrix} - 9 \begin{vmatrix} 2 & -6 \\ 3 & -9 \end{vmatrix} - 1 \begin{vmatrix} 2 & -3 \\ 3 & -5 \end{vmatrix} \] Calculating these smaller 2x2 determinants: - First: \((-3)(-9) - (-6)(-5) = 27 - 30 = -3\) - Second: \((2)(-9) - (-6)(3) = -18 + 18 = 0\) - Third: \((2)(-5) - (-3)(3) = -10 + 9 = -1\) Now substituting back to find \( D \): \[ D = -4(-3) - 9(0) - 1(-1) = 12 + 0 + 1 = 13 \] ### 2. Calculate the determinant \( D_x \): Replace the first column of \( A \) with the constants from the equations: \[ D_x = \begin{vmatrix} -8 & 9 & -1 \\ 4 & -3 & -6 \\ 6 & -5 & -9 \end{vmatrix} \] Calculating it: \[ D_x = -8 \begin{vmatrix} -3 & -6 \\ -5 & -9 \end{vmatrix} - 9 \begin{vmatrix} 4 & -6 \\ 6 & -9 \end{vmatrix} - 1 \begin{vmatrix} 4 & -3 \\ 6 & -5 \end{vmatrix} \] Calculating the smaller 2x2 determinants: - First: \((-3)(-9) - (-6)(-5) = 27 - 30 = -3\) - Second: \((4)(-9) - (-6)(6) = -36 + 36 = 0\) - Third: \((4)(-5) - (-3)(6) = -20 + 18 = -2\) Now substituting back to find \( D_x \): \[ D_x = -8(-3) - 9(0) - 1(-2) = 24 + 0 + 2 = 26 \] ### 3. Calculate the determinant \( D_y \): Replace the second column of \( A \): \[ D_y = \begin{vmatrix} -4 & -8 & -1 \\ 2 & 4 & -6 \\ 3 & 6 & -9 \end{vmatrix} \] Calculating it: \[ D_y = -4 \begin{vmatrix} 4 & -6 \\ 6 & -9 \end{vmatrix} - (-8) \begin{vmatrix} 2 & -6 \\ 3 & -9 \end{vmatrix} - 1 \begin{vmatrix} 2 & 4 \\ 3 & 6 \end{vmatrix} \] Calculating the smaller 2x2 determinants: - First: \((4)(-9) - (-6)(6) = -36 + 36 = 0\) - Second: \((2)(-9) - (-6)(3) = -18 + 18 = 0\) - Third: \((2)(6) - (4)(3) = 12 - 12 = 0\) Now substituting back to find \( D_y \): \[ D_y = -4(0) + 8(0) - 0 = 0 \] ### 4. Calculate the determinant \( D_z \): Replace the third column of \( A \): \[ D_z = \begin{vmatrix} -4 & 9 & -8 \\ 2